Profile of Hematological Oncology Patients at Purbanchal Cancer Hospital, Nepal: A Retrospective Study - Singh, Ishwor Man; Rattan, Rajit; Yadav, Birendra Kumar (Medical Journal of Eastern Nepal, 2025)
Background: Hematological malignancies, including leukemias, lymphomas, and multiple myeloma, pose a growing burden in developing countries like Nepal, yet regional data remain scarce. This study profiles patients with hematological malignancies at Purbanchal Cancer Hospital, a referral center in eastern Nepal, to inform clinical practice and research.Methods: A retrospective analysis was conducted on 249 patients diagnosed with haematological malignancies at Purbanchal Cancer Hospital from January 1, 2022, to December 31, 2024. Data on age, sex, diagnosis, geographical origin, relapse status, and genetic mutations were extracted from medical records. Descriptive statistics were used to analyze frequency distributions, age-sex patterns, and notable trends.Results: Out of 249 patients (age 2–99 years), 55.4% were male. Multiple myeloma (MM) was the most frequent diagnosis (18.9%), followed by non-Hodgkin lymphoma (NHL, 17.7%) and acute myeloid leukemia (AML, 17.3%). Acute lymphoblastic leukemia (ALL) predominated in children (71.8% of 0–18 years), while MM and AML were frequent in adults (19–60 years) and the elderly (61+ years). AML showed a high relapse rate (23.3%), with FLT3-ITD (6 cases) and NPM1 (5 cases) noted. ALL included BCR-ABL-positive cases (3), and myeloproliferative neoplasms featured JAK2 mutations (11). Most patients (59.4%) were from Jhapa district.Conclusion: MM emerged as the leading hematological malignancy at Purbanchal Cancer Hospital, contrasting with prior Nepalese studies that reported AML as most prevalent—possibly due to referral patterns. The high relapse rate in AML and the presence of actionable mutations highlight the need for expanded molecular testing and improved therapeutic strategies. Future research should include survival data and population-based studies to refine regional cancer strategies.